Quantitative evaluation of IVL: based on the tunica media gypsum calcification model and a prospective animal study - Zongwei Liu; Zongwei Liu; Zongwei Liu; Chuang Xu; Chuang Xu; Bin Zhao; Bin Zhao; Jiayin Guo; Jiayin Guo; Jingzhong Song; Jingzhong Song; Jiaxue Bi; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIntravascular lithotripsy (IVL), an emerging adjunctive therapeutic modality, demonstrates potential in managing severely calcified lesions. However, its quantitative efficiency in disrupting calcifications with different characteristics, as well as the degree of damage to normal arteries, remains to be confirmed.ObjectivesThis study aimed to: (i) quantitatively evaluate the efficacy of IVL in disrupting different types of calcifications, and (ii) assess the impact of IVL on normal vascular structures.MethodsThe gypsum models with different thicknesses and eccentricities were used to evaluate the effectiveness of IVL in disrupting calcifications with different characteristics. In vivo experiments involved iliofemoral arterial segments of nine Yorkshire experimental swine that were subjected to IVL and PTA working balloons, respectively. In vitro effectiveness of IVL was evaluated using the number of disrupted gypsum rings based on the gypsum models. In vivo effectiveness and safety of IVL were evaluated by digital subtraction angiography (DSA), light microscopy, and immunofluorescence staining based on the experimental swine at 0, 7, and 28 days.ResultsThe gypsum models revealed that the 1.04:1 oversized IVL working balloon could provide an optimal tightness between the balloon and the artery wall. The DSA imaging results showed that IVL significantly increased the immediate treated artery's diameter at +27.12 ± 10.23% compared to the PTA working balloon at +13.72 ± 7.66% in all experimental animals (n = 9, p = 0.0063). The imaging results revealed that IVL treatment significantly alleviated the lumen loss rate of treated arteries compared to the PTA working balloon at 7 (1.10 ± 0.58% vs. 3.27 ± 0.66%) and 28 (4.90 ± 1.60% vs. 10.10 ± 1.53%) days postoperatively (p < 0.05). Histopathological analysis showed the IVL treatment did not increase the inflammatory status, synthesis of collagen, and other artery wall characteristics at 0, 7, and 28 days postoperatively. The immunofluorescence staining results revealed that IVL treatment did not significantly decrease the proportion of smooth muscle cells and endothelial cells in the treated artery.ConclusionOur experiment revealed that the IVL device has good therapeutic effects on different characteristics of calcifications hiding in the tunica media and with good biological safety.